Rotation Periods of Nearby, Mid-to-late M Dwarfs from the MEarth Project. Issue Volume 10:Issue S314(2015) (November 2015) - Newton, Elisabeth R.; Irwin, Jonathan; Charbonneau, David; Berta-Thomspon, Zachary K.; West, Andrew A.
Abstract: Field stars provide important constraints for the late stages of stars' angular momentum evolution. We measured rotation periods ranging from 0.1 to 150 days for approximately 450 mid-to-late M dwarfs using photometry from the MEarth transiting planet survey. We use parallaxes, proper motions, and radial velocities to calculate galactic kinematics for these solar neighborhood M dwarfs. The velocity dispersions increase towards longer rotation periods, indicating that there is a relationship between rotation and age for these stars.